2012
DOI: 10.1002/art.34339
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: A phase IIa, randomized, double‐blind, placebo‐controlled trial of apilimod mesylate, an interleukin‐12/interleukin‐23 inhibitor, in patients with rheumatoid arthritis

Abstract: Objective. To investigate the safety, tolerability, pharmacokinetics, and efficacy of apilimod mesylate, an oral interleukin-12 (IL-12)/IL-23 inhibitor, in patients with rheumatoid arthritis (RA).Methods. We performed a phase IIa, randomized, double-blind, placebo-controlled proof-of-concept study of apilimod, in combination with methotrexate, in 29 patients with active RA ( Results. While only mild adverse events were observed in stages 1 and 2, in stage 3, all patients experienced headache and/or nausea. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 16 publications
1
50
0
3
Order By: Relevance
“…This is supported by our findings in eRA, where an inverse association was observed between the duration of symptoms prior to diagnosis and plasma levels of IL-23. Further support is found in a study by Krausz et al, in which no effect was observed in RA patients with established disease treated with anti-p40 (IL-23/IL-12) (2,15). Considering that IL-23 is important in the establishment of the autoimmune process, signs of its involvement should therefore be observed among patients in the very early phases of disease development.…”
Section: Discussionmentioning
confidence: 74%
“…This is supported by our findings in eRA, where an inverse association was observed between the duration of symptoms prior to diagnosis and plasma levels of IL-23. Further support is found in a study by Krausz et al, in which no effect was observed in RA patients with established disease treated with anti-p40 (IL-23/IL-12) (2,15). Considering that IL-23 is important in the establishment of the autoimmune process, signs of its involvement should therefore be observed among patients in the very early phases of disease development.…”
Section: Discussionmentioning
confidence: 74%
“…Neutralization of p40 would prevent function of both IL-23 and IL-12 but if such treatment would be of benefit to patients with RA is not known. To the best of our knowledge, ustekinumab has not been tested in RA patients, but an inhibitor of IL-12 and IL-23 signaling, apilimod mesylate, was not able to reduce proinflammatory cytokine levels or immune infiltrates in inflamed synovial tissue when administered in combination with methotrexate [67]. …”
Section: Rheumatoid Arthritismentioning
confidence: 85%
“…The level of interest in this target can be seen from the fact that 15 different IL23R antagonists are now reported to be in clinical or pre-clinical development [182] . Recent clinical studies associated with IL-23 inhibition in arthritis include the use of apilimod mesylate, an orally administered inhibitor of IL-12/IL-23 in RA [183] . Ustekinumab and briakinumab, fully human mAbs directed against the p40, are currently in phase 2 trials.…”
Section: Il-2 Superfamilymentioning
confidence: 99%